Circular economy and ecologically sustainable behaviour in the light of financial constraints: quantitative results from Austria - Lukas Richter; Lukas Richter; Mohammed Qasim Khattab (Frontiers in Sustainability)
IntroductionThe circular economy (CE) has been proposed as a model for promoting both sustainability and economic growth, yet its social dimensions remain underexplored. This study investigates the relationship between financial constraints and the adoption of CE strategies, aiming to assess whether financial hardship influences individuals’ ability to engage in sustainable practices.MethodsThe study utilises quantitative survey data from Austria (n = 1,003) collected in June 2022. A secondary analysis was conducted using bivariate and multivariate statistical techniques, including Welch-ANOVA and binary logistic regression. The study examines four CE strategies—reduce, share, second-hand, and repair—across product categories such as clothing, electronics, furniture, and toys. The key independent variable is financial constrain, while controls include willingness to engage in sustainable behaviour, accessibility of CE infrastructure and socio-demographic factors.ResultsThe findings indicate that financial constraints significantly impact engagement in some CE strategies. Individuals facing financial difficulties are more likely to participate in cost-saving strategies such as buying second-hand goods (e.g., clothes OR = 1.38, electronics OR = 1.39) or repairing toys (OR = 1.48). Willingness to engage in sustainable behaviour is the strongest predictor across all strategies, while accessibility plays also a crucial role in adoption. Surprisingly, environmental awareness does not significantly predict actual sustainable behaviour, highlighting a gap between intention and action.DiscussionThe results suggest that financial constraints can act as both a barrier and a driver for sustainable behaviour. While affordability enhances participation in second-hand markets, financial barriers may hinder engagement in repair and sharing models. The study raises concerns about ‘double injustice,’ where low-income individuals not only bear greater environmental risks but also face challenges in accessing sustainable solutions.